Political party elite and election-related violence in Nigeria: The nexus and implications for democracy and governance - Ahmed Olawale Moliki (Universitas Trunojoyo Madura, 2021)
Failure to conduct violence-free elections in Nigeria has frequently reflected in the writings of local and foreign election observers and monitoring groups. Previous studies have devoted much attention to the consequences of electoral violence on sustenance and consolidation of democracy but less attention has been paid to the role political party elite play in this violence. This study examined the role of political party elite in election-related violence in Nigeria, 2011-2019. It equally assessed its nexus and implications for democracy and governance. The study utilized documentary research method using qualitative documentary analysis to analyze the data obtained from secondary sources following four-step approach. Findings revealed that political party elite exerted greater influence on politically-sponsored thugs, who were utilized to perpetrate election-related violence due to zerosum game, winners-takes-all syndrome, and non-punishment of electoral offenders with far-reaching implications for popular participation, free, fair and credible election, party politics, leadership legitimacy and stable polity. The study submitted that curbing party elite-sponsored electoral violence requires that the Independent National Electoral Commission (INEC) and the National Assembly wake up to their responsibility of ensuring strict enforcement of laws for electoral offences as this would deter both sponsors and perpetrators from engaging in violence during election.